2019
DOI: 10.1016/j.wjorl.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Determining the utility of standard hospital microbiology testing: Comparing standard microbiology cultures with DNA sequence analysis in patients with chronic sinusitis

Abstract: Objective To demonstrate DNA sequencing analysis (DNAsa) of sinus cultures in patients with CRS is a reliable method of detecting pathogens in polymicrobial CRS infections. Methods After obtaining Institutional Review Board approval for this prospective cohort study, we selected a random sample of 50 patients with CRS at Medstar Georgetown University Hospital between September 2016 and March 2017. We defined CRS as a history of rhinosinusitis refractory to maximal medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, the simple method of nasal bacterial culture limits the understanding of the pathological mechanism of CRSwNP, 14 and molecular diagnosis of submucosal bacterial clones and histopathological observation are more sensitive and diagnostic than simple bacterial culture. 26,27 LPS is considered to be a trigger for inflammatory responses. LPS activates inflammatory signaling pathways mainly through the classic Toll-like receptor 4 (TLR4) receptor on the cell surface, stimulating the body to produce inflammatory factors, and leading to tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the simple method of nasal bacterial culture limits the understanding of the pathological mechanism of CRSwNP, 14 and molecular diagnosis of submucosal bacterial clones and histopathological observation are more sensitive and diagnostic than simple bacterial culture. 26,27 LPS is considered to be a trigger for inflammatory responses. LPS activates inflammatory signaling pathways mainly through the classic Toll-like receptor 4 (TLR4) receptor on the cell surface, stimulating the body to produce inflammatory factors, and leading to tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…This result may be an important reason for the inconsistency in the results. Therefore, the simple method of nasal bacterial culture limits the understanding of the pathological mechanism of CRSwNP, 14 and molecular diagnosis of submucosal bacterial clones and histopathological observation are more sensitive and diagnostic than simple bacterial culture 26,27 …”
Section: Discussionmentioning
confidence: 99%
“…The 16S ribosomal RNA is highly conserved within bacterial and fungal species and can therefore be detected for microbial identification and quantification. 16 Pyrosequencing is a method of DNA sequencing in which inorganic pyrophosphate is released with the DNA polymerase reaction and incorporation of each nucleotide. Pyrophosphate is converted to adenosine triphosphate (ATP) by sulfurylase, and a proportionate amount of light is produced by luciferase.…”
Section: Methodsmentioning
confidence: 99%
“…However, whether it can be used for the differential diagnosis of odontogenic maxillary sinusitis from maxillary sinus needs further study [22][23][24][25][26][27][28], whereas cytokines and chemokines are currently detected in local tissues, and detection in serum is relatively rare. Rapoport et al tried to compare microbial DNA probes with a conventional microbial culture to find the pathogenic microbial as well as chemosensitivity and found that DNA probes are more accurate and reliable than traditional methods [29]. However, the detection efficiency is limited and needs further expansion.…”
Section: Diagnosismentioning
confidence: 99%